Evaluation of Animal-Based Indicators to Be Used in a Welfare Assessment Protocol for Sheep - Richmond, Susan E.; Wemelsfelder, Francoise; de Heredia, Ina Beltran; Ruiz, Roberto; Canali, Elisabetta; Dwyer, Cathy M. (Frontiers in Veterinary Science, 2017)
Sheep are managed under a variety of different environments (continually outdoors, partially outdoors with seasonal or diurnal variation, continuously indoors) and for different purposes, which makes assessing welfare challenging. This diversity means that resource-based indicators are not particularly useful and thus a welfare assessment scheme for sheep, focusing on animal-based indicators, was developed. We focus specifically on ewes, as the most numerous group of sheep present on farm, although many of the indicators may also have relevance to adult male sheep. Using the Welfare Quality® framework of four Principles and 12 Criteria, we considered the validity, reliability and feasibility of 46 putative animal-based indicators for these criteria, derived from the literature. Where animal-based indicators were potentially unreliably or were not considered feasible, we also considered the resource-based indicators of access to water, stocking density and floor slipperiness. With the exception of the criteria ‘Absence of prolonged thirst’ we suggest at least one animal-based indicator for each welfare criterion. As a minimum, face validity was available for all indicators, however for many we found evidence of convergent validity, and discriminant validity (e.g. lameness as measured by gait score, body condition score). The reliability of most of the physical and health measures has been tested in the field and found to be appropriate for use in welfare assessment. However, for the majority of the proposed behavioural indicators (lying synchrony, social withdrawal, postures associated with pain, vocalisations, stereotypy, vigilance, response to surprise and human approach test) this still needs to be tested. In conclusion, the comprehensive assessment of sheep welfare through largely animal-based measures is supported by the literature through the use of indicators focusing on specific aspects of sheep biology. Further work is required for some indicators to ensure that measures are reliable when used in commercial settings.